Inactivation Efficacy of 405 nm LED Against Cronobacter sakazakii Biofilm - Huang, Yixiao; Pei, Quanwei; Deng, Ruisha; Zheng, Xiaoying; Guo, Jialu; Guo, Du; Yang, Yanpeng; Liang, Sen; Shi, Chao (Frontiers in Microbiology, 2020)
The objectives of this study were to evaluate the inactivation efficacy of a 405-nm light-emitting diode (LED) against Cronobacter sakazakii biofilm formed on stainless steel and to determine the sensitivity change of illuminated biofilm to food industrial disinfectants. The results showed that LED illumination significantly reduced the population of viable biofilm cells, showing reduction of 2.0 log (25°C), 2.5 log (10°C) and 2.0 log (4°C) between the non-illuminated and LED-illuminated groups at 4 h. Images of confocal laser scanning microscopy and scanning electron microscopy revealed the architectural damage to the biofilm caused by LED illumination, which involved destruction of the stereoscopic conformation of the biofilm. Moreover, the loss of biofilm components (mainly polysaccharide and protein) was revealed by attenuated total reflection Fourier-transformed infrared spectroscopy, and the downregulation of genes involved in C. sakazakii biofilm formation was confirmed by real time quantitative PCR analysis, with greatest difference observed in fliD. In addition, the sensitivity of illuminated-biofilm cells to disinfectant treatment was found to significantly increased, showing the greatest sensitivity change with 1.5 log reduction between non-LED and LED treatment biofilms in the CHX-treated group. These results indicated that 405 nm LED illumination was effective at inactivating C. sakazakii biofilm adhering to stainless steel. Therefore, the present study suggests the potential of 405 nm LED technology in controlling C. sakazakii biofilms in food processing and storage, minimizing the risk of contamination.